Analisis Dinamika Lalu Lintas Menggunakan Model Petri Net - Ruvita Iffahtur Pertiwi; Fitria Khasanah (Universitas Sarjanawiyata Tamansiswa, 2026)
This study analyzes the dynamics of traffic flow in the heritage area of Malang City using the Petri Net model. In contrast to common Petri Net studies that focus on urban traffic light optimization, this research specifically models the characteristics of a heritage area characterized by physical space constraints and its dual function as a tourist destination. The study focuses on three main observation points with vehicle volume data collection. The Petri Net model was developed to represent the relationships between traffic nodes and simulate traffic behavior under various conditions. The primary scientific contribution of this research lies in the integration of real-time field data with the incidence matrix to identify discrete flow behavior at critical non-signaled point. Simulation results reveal specific peak hours and demonstrate the model’s capability in illustrating traffic flow transitions and potential bottlenecks. These findings provide a technical database for the Malang City Government in designing one-way traffic engineering and parking management within the cultural heritage corridor.